The indissociability between playing, caring and educating in Elementary School (Research, Society and Development, 2017)
Elementary School is the first phase of the brazilian basic education period in which children spend most of their time, with respect to their rights and the need to understand that there are fundamental and indispensable acts in the pedagogical practice. This study is justified by the indissociability between the caring, playing and educating practices, as well as the need of constantly providing them to children in education. The general objective of this study was to understand that children want to discover and unveil the mysteries and curiosities the world provides them and that, in order to do so, a pedagogical intervention is needed, aiming at encouraging such discover and the children’s multiple development. By means of a bibliographic review, we discussed how the three practices of caring, playing and educating are associated, as well as how necessary it is to work and encourage these practices in children, since very young, always aiming at their learning and comprehensive development. In this article, we discussed the pedagogical practice of Elementary School teachers, the act of caring and educating simultaneously and the importance of playing, as well as considering this as something serious and fundamental in childhood. As educators of children, teachers need to understand that situations in class will always involve caring and educating. Just as only playing is not enough, this moment must be interactive, explorative and with good quality, knowing that playing time is an extremely educational moment for children. In this study, we perceived that Elementary School is one of the great responsible elements for children’s social formation, as well as one of the leading elements towards their multiple development. Thus, it is necessary to understand the needs of this infant phase, always aiming at children’s social and comprehensive formation.